Pelatihan MC (Master of Ceremony) Berbahasa Inggris bagi Siswa SMK Tunas Bangsa Tawangsari Sukoharjo - Ratih Wijayava; Nunun Tri Widarwati; Purwani Indri Astuti (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service project aims to enhance the English Master of Ceremony (MC) skills of students at SMK Tunas Bangsa Tawangsari, addressing the demand for proficient hosts in both formal and informal events. The methodology involved theoretical presentations, practical simulations, and evaluation through pre-tests and post-tests. The results indicated a significant improvement in understanding, with average scores rising from 85.71 in the pre-test to 95.87 in the post-test, marking a 15.28% increase. Furthermore, the students' practical performance achieved an average score of 81.4, falling into the